Prevalence of, and factors associated with, diabetes mellitus in people with severe mental illness attending a multidisciplinary, outpatient cardiometabolic health assessment service. Issue 1 (18th January 2023) - Lambert, Tim; Middleton, Tim; Chen, Roger; Sureshkumar, Premala
Abstract : Introduction: Evaluate the prevalence of, and factors associated with, diabetes in people with severe mental illness (SMI) attending the Collaborative Centre for Cardiometabolic Health in Psychosis (ccCHiP) tertiary referral clinics. Research design and methods: Adult patients attending an initial ccCHiP clinic consultation (2014–2019) were studied. Diabetes was defined by an hemoglobin A1c of ≥6.5%, fasting blood glucose of ≥7.0 mmol/L, or a self-reported diagnosis of diabetes and prescription of antihyperglycemic medication. Results: Over 5 years, 1402 individuals attended a baseline consultation. Mean age of 43.9±12.8 years, 63.1% male and 63.5% had a diagnosis of schizophrenia. Prevalence of diabetes was 23.0% (n=322); an additional 19.5% fulfilled criteria for pre-diabetes. Of those with diabetes, 15.8% were newly diagnosed. Of those with pre-existing diabetes, 84.5% were receiving treatment with antihyperglycemic medication. Over 94% of individuals with diabetes had dyslipidemia; half were current smokers; and 46.4% reported sedentary behavior. On multivariate analysis, diabetes was associated with older age, Aboriginal, Indian or Middle Eastern maternal ethnicity, elevated waist-to-height ratio, family history of diabetes and use of antipsychotic medication. Conclusion: Prevalence of diabetes mellitus in this multiethnic cohort with SMI is significantly higher than the Australian population. Targeted interventions via an assertive integrated approach are required to optimize cardiometabolic health in this population.